Experimental study of cognitive aspects affecting human performance in manual assembly. Issue 1 (1st January 2017) - Brolin, Anna; Thorvald, Peter; Case, Keith
Abstract: This study investigate different ways of presenting material and information at workstations while using mixed assembly mode with product variants. The experimental set up annotated an assembly line involving 36 subjects. The material presentation factor involved the use of a material rack compared to using an unstructured kit as well as a structured kit. The information presentation factor involved using a text and number instruction compared to a photograph instruction, and situations with and without component variation were considered. Results show  that assembly times and workload ratings were lower when using a kit, whereas using a material rack resulted in perceived decreased workflow and increased stress and frustration. Moreover, assembly times and workload ratings were lower when using photographs, whereas using text and numbers increased mental workload. The results could be useful when planning work places and production systems in order to obtain a better workflow and an increased human performance.